Articulated rods – a novel class of molecular rods based on oligospiroketals (OSK) - Wessig, Pablo; Merkel, Roswitha; Müller, Peter (Beilstein Journal of Organic Chemistry, 2015)
We developed a new type of molecular rods consisting of two (or more) rigid units linked by a flexible joint. Consequently we called these constructs articulated rods (ARs). The syntheses of ARs were carried out by a flexible and modular approach providing access to a number of compounds with various functionalizations in terminal positions. First applications were presented with pyrene, cinnamoyl and anthracenyl labelled ARs.
Keywords: articulated rods; click chemistry; molecular rods; oligospiroketals; pyrene excimer